Multicultural education and its reflections - (:unkn) unknown (HACETTEPE UNIV, 2008)
It is expected that individuals should be in an interaction with different cultural groups and improve positive attitudes in their interaction, in the modem societies. Therefore, while developed countries get solutions for the problems about education, they also utilize the studies about multicultural education. Multicultural education, focuses on the different learning environments for making students tolerate different cultures. So, the teachers should create leaming environments which make students respect the values of other cultural groups and remove their prejudices about different cultures and admit seriously the differences which are richness for the humanity. For this reason, in this study, the development process of multicultural education and its reflections to learning environments are tried to be examined.
Keywords: multicultural education; learning; curriculum